Korean Dramas: Viewing And Liking On Malaysian Youths’ Behavioral Intentions - Loke, Jingyi (2020)
The purpose of this quantitative study is to examine the influence of South Korean dramas on behavioral intentions toward South Korea among Malaysian youth. Using the cultivation theory as a guideline, the influence of South Korean dramas on the viewers’ behavioral intentions toward South Korea is explained using the watching, likings of South Korean drama and attitude toward South Korea. A total of 547 samples were collected from Malaysian youths via online survey through social media (Twitter). The results suggested that Malaysian youths’ behavioral intentions toward Korea is positively influenced by the viewing, likings of South Korean dramas and attitude toward South Korea. The viewing and positive feelings toward South Korean dramas are able to yield positive attitude toward South Korea. Furthermore, attitude toward South Korea is found out to be a partial mediator in the indirect effect of viewing and likings of South Korean dramas. Implications of the study findings are discussed in this study.